The first complete mitochondrial genome data of hippocampus kuda originating from Malaysia - Jahari, P. N. S. (Elsevier Inc., 2020)
The spotted seahorse, Hippocampus kuda population is exponentially decreasing globally due to habitat loss contributed by massive coastal urbanization as well as its large exploitation for Chinese herbal medicine. Genomic data would be highly useful to improve biomonitoring of seahorse populations in Malaysia via the usage of non-invasive approaches such as water environmental DNA. Here we report the first complete mitogenome of two H. kuda individuals originating from Malaysia, generated using BGISEQ-500RS sequencer. The lengths of both mitogenomes are 16,529bp, consisting of 13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes, and a control region. The overall base composition was 32.46% for A, 29.40% for T, 14.73% for G and 23.41% for C with AT rich features (61.86%). The gene organization of Malaysian H. kuda were similar to that of most teleost species. A phylogenetic analysis of the genome against mtDNA data from other Hippocampus species showed that Malaysian H. kuda samples clustered with H. capensis, H. reidi and H. kuda. Notably however, analysis of the data using BLASTn revealed they had 99.18% similarity to H. capensis, and only 97.66% to H. kuda and H. reidi, which are all part of the unresolved H. kuda complex. The mitogenomes are deposited in Genbank under the accession number MT221436 (HK1) and MT221436 (HK2).